Diagnostic performance of abbreviated non-contrast liver MRI for detecting synchronous colorectal liver metastases - Puwitch Charoenchue; Kamon Rajchakom; Amonlaya Amantakul; Suwalee Pojchamarnwiputh; Chanon Thanaphakpaisarn; Wittanee Na Chiangmai; Tanin Lertsiriladakul (PLoS ONE, 2026)
Background Colorectal cancer (CRC) is a leading malignancy, and colorectal liver metastases (CRLM) are common. Accurate detection is critical for staging and treatment planning. Although contrast-enhanced MRI is the reference standard, its use is limited by cost, longer examination time, and contraindications such as renal impairment or prior severe allergic reactions. This study aimed to evaluate the diagnostic performance of an abbreviated non-contrast liver MRI protocol for detecting CRLM and to compare performance between experienced and in-training readers. Materials and methods In this retrospective study, 87 patients with CRC who underwent liver MRI between January 2014 and March 2024 were included. The abbreviated non-contrast protocol comprised T1-weighted imaging (T1WI), T2-weighted imaging (T2WI), and diffusion-weighted imaging (DWI). Two independent readers evaluated the images using a 4-point confidence scale, which was dichotomized for analysis. Sensitivity, specificity, predictive values, and accuracy were calculated, and interobserver agreement was assessed using weighted kappa. Contrast-enhanced MRI served as the reference standard. Results The abbreviated non-contrast MRI demonstrated high diagnostic performance. Sensitivity and specificity were 94.1% and 88.7% for the abdominal radiologist, and 91.2% and 96.2% for the oncologic imaging fellow. The area under the receiver operating characteristic curve (AUROC) was 0.93 and 0.94, respectively, with no significant difference between readers ( p = 0.494). Interobserver agreement was substantial (weighted κ = 0.74). Conclusion Non-contrast MRI demonstrated reliable diagnostic performance with substantial interobserver agreement for CRLM detection, suggesting its potential clinical applicability. While contrast-enhanced MRI remains the standard, non-contrast MRI may be a feasible alternative in select cases. Further large-scale validation is necessary before broader clinical adoption.